Tanggung Jawab PPAT Terhadap Pendaftaran Peralihan Hak Atas Tanah yang Menjadi Objek Sengketa Ditinjau dari PP Nomor 24 Tahun 2016 - Iwan Chandra; Agus Salim; Belly Isnaeni (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explains the legal consequences of registering the transfer of land rights with a PPAT deed that becomes the object of a dispute and the responsibilities of PPAT in the context of Government Regulation Number 24 of 2016 concerning the Position Regulation of the Land Deed Official. The research is conducted using a normative juridical approach with legislative, conceptual, and case approaches. A qualitative method is used to analyze data descriptively with authority theory, liability theory, and legal certainty theory. Problems arise when the registration of the transfer of land rights is recorded in the land book because the rights become the object of a dispute, resulting in the return of documents by the land office. There is no regulation regarding the responsibility of PPAT for the return of these documents. The legal consequence of registering the transfer of rights that become the object of a dispute is the rejection of the registration by the local land office, preventing registration or changes to land data during the blocking period. PPAT is personally responsible for the execution of their duties and positions in making deeds, as stipulated in Article 55 of the Head of BPN Regulation No. 1 of 2006, which states that "PPAT is personally responsible for the execution of their duties and positions in making each deed." Additionally, PPAT also has administrative and civil responsibilities.